2015
DOI: 10.1016/j.clay.2015.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliation and intercalation of montmorillonite by small peptides

Abstract: Understanding structural changes in clay minerals induced by complexation with organic matter is relevant to soil science and agricultural applications. In this study, the effect of peptide storage in montmorillonite and the thermal stability of peptide-clay complexes was examined through characterization by X-ray diffraction (XRD), electron microscopy, UV absorption, and thermogravimetric analysis (TGA). XRD analysis of small peptide-montmorillonite clay complexes produced profiles consisting of reflections a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…[7][8][9][10][11][12][13][14][15][16][17][18] In this study, we demonstrated that co-spray-drying of lactose and Na-MMT leads to lactose intercalation,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11][12][13][14][15][16][17][18] In this study, we demonstrated that co-spray-drying of lactose and Na-MMT leads to lactose intercalation,…”
Section: Discussionmentioning
confidence: 99%
“…5 There is significant amount of published research on organic polymer-clay nanocomposites, but only few report on MMT combined with low-molecular-weight organic compounds including peptides and amino acids. [7][8][9][10][11][12][13][14][15][16][17][18][19] In these reports, the most important mechanism involved in intercalation into MMT is cationic exchange. 7-9, 12, 13, 19 Anionic and nonionic compounds have also been demonstrated to interact with MMT.…”
Section: Introductionmentioning
confidence: 99%
“…This may suggest preferential adsorption of N-containing biomolecules [8,14,45] on illite and montmorillonite. Montmorillonitic soils retain peptides and become enriched with amine-N [46,47]. Microbial residues such as secretions and necromass are a component of mineral-associated SOM [31,48] although Vogel et al [49] reported that illite retained more microbial-derived C and N than montmorillonite.…”
Section: Residue-derived C and N Retention In Mineral-associated Sommentioning
confidence: 99%
“…It has been shown that MMT is a 2:1-type layered clay mineral with a sandwiched structure composed of two 2D platelets and interlayer cations (i.e., Na + , Ca 2+ , Mg 2+ ). The strong hydrogen-binding and electrostatic interaction, and van der Waals forces between two platelets make MMT difficult to be exfoliated and tend to be present in a form of agglomeration (Zhang et al, 2014; Block et al, 2015; Liu et al, 2016). In comparison, natural 1D rod-like nanoclays are easy to be dispersed as nanoscale size, and showed great potential to be used to develop polymer/nanoclays composites (Nikolic et al, 2017; Ajmal et al, 2018; Shankar et al, 2018; Zhang P. et al, 2018).…”
Section: Introductionmentioning
confidence: 99%